Environmental performance, Islamic corporate governance, and liquidity's impact on financial performance with sustainability reporting as a mediating factor - Rismawati, Artias; Bawono, Anton (Nur Science Institute, 2022)
This study aims to determine the effect of environmental performance, Islamic corporate governance, and liquidity on financial performance in companies listed on ISSI and perform a Performance Assessment Program in Environmental Management with sustainability reporting as an intervening variable. This type of research is quantitative and uses secondary data obtained through each company's website and the Ministry of Environment and Forestry of the Republic of Indonesia 2014-2021. The analytical tool used is path analysis. The results of this study show that the environmental performance variable has a significant positive effect on financial performance. Islamic corporate governance and liquidity variables do not affect financial performance. Then the environmental performance variables, Islamic corporate governance, and liquidity do not affect sustainability reporting. Sustainability reporting cannot mediate the relationship between environmental performance, Islamic corporate governance, and liquidity on financial performance. However, the sustainability reporting variable significantly negatively affects financial performance.